Performance evaluation of the PET component of a hybrid PET/CT-ultrafast ultrasound imaging instrument. (21st September 2018) - Perez-Liva, Mailyn; Viel, Thomas; Yoganathan, Thulaciga; Garofalakis, Anikitos; Sourdon, Joevin; Facchin, Caterina; Tanter, Mickael; Provost, Jean; Tavitian, Bertrand
Abstract: We recently introduced a hybrid imaging instrument, PETRUS, based on a combination of positron emission tomography (PET) for molecular imaging, x-ray computed tomography (CT) for anatomical imaging, co-registration and attenuation correction, and ultrafast ultrasound imaging (UUI) for motion-correction, hemodynamic and biomechanical imaging. In order to ensure a precise co-registration of simultaneous PET-UUI acquisitions, ultrasound probes attached to an ultrafast ultrasound scanner are operated in the field of view (FOV) of a small animal PET/CT scanner using a remote-controlled micro-positioner. Here we explore the effect of the presence of ultrasound probes on PET image quality. We compare the performance of PET and image quality with and without the presence of probes in the PET field of view, both in vitro following the NEMA-NU-4-2008 standard protocol, and in vivo in small animals. Overall, deviations in the quality of images acquired with and without the ultrasound probes were under 10% and under 7% for the NEMA protocol and in vivo tests, respectively. Our results demonstrate the capability of the PETRUS device to acquire multimodal images in vivo without significant degradation of image quality.